GENERALISED CESARO-ORLICZ DOUBLE SEQUENCE SPACES OVER N-NORMED SPACES - Pandoh, S.; Raj, K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2016)
This article is an attempt to highlight wide-ranging Cesaro-Orlicz double difference sequence spaces over n-normed spaces. The aim here lies in analyzing some topological properties and inclusion relations between these spaces.